Preparation process of high-barrier recyclable PE packaging film
By synthesizing flame retardant crosslinked monomers in PE packaging film, modifying graphene nanosheets, and compounding them with ethylene vinyl alcohol copolymer, combined with eleven-layer coextrusion blow molding process, the recycling and utilization of existing PE packaging films is solved. Difficulties and flammable problems have achieved the improvement of high barrier, flame retardant and light retardant performance, and improved the recovery rate and safety of packaging film.
Patent Information
- Application Number
- CN202411282905.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-13
Smart Images

Figure CN119239088A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of research and development of functional packaging materials, and specifically to a preparation process of a high-barrier recyclable PE packaging film. Background Art
[0002] Plastic packaging has become one of the mainstream forms of dairy product packaging due to its advantages such as light weight, transparency, shatterproof and easy to shape. Among them, PE packaging film is non-toxic and tasteless, has outstanding chemical stability, outstanding low temperature resistance, excellent electrical insulation and low water absorption, and is the most widely used in the field of dairy product packaging. Currently, PE packaging products on the market are often made of multiple layers or multiple materials. In the composition of the composite material, there are not only plastic layers, but also aluminum foil, coating and other materials that are difficult to separate. This makes the sorting and classification process of PE packaging film after use cumbersome and difficult, and the recycling rate is low. Random discarding and improper disposal will cause serious environmental pollution and waste of resources.
[0003] Multi-layer co-extruded high-barrier single PE plastic packaging film does not need to be sorted when recycled and can be recycled repeatedly, which has gradually become a development trend in the packaging industry. For example, the Chinese patent with publication number CN115447241A prepared a high-barrier single PE recyclable material packaging film through a multi-layer co-extrusion method, which has high recycling efficiency and practical application value.
[0004] In the prior art, there have been reports on using nano-sheet materials (graphene, silicate, boron nitride) with large specific surface area as polymer fillers to improve the mechanical properties and barrier properties of PE packaging materials. In addition, traditional PE packaging films are very easy to burn, have high safety risks, and have poor flame retardant properties, so they often need to be flame-retardantly modified to meet actual use needs. Summary of the invention
[0005] The present invention develops a novel eleven-layer co-extruded film made of a single PE material based on a unique interlayer formula design. The eleven-layer co-extruded film has very excellent barrier properties and can be used as a dairy product packaging film.
[0006] A preparation process of a high-barrier recyclable PE packaging film comprises the following steps:
[0007] Step 1: Synthesize a flame retardant cross-linking monomer, the chemical structure of which is:
[0008]
[0009] Step 2: Modifying the hydroxylated graphene powder with a flame-retardant cross-linking monomer to obtain a modified graphene nanosheet, and uniformly dispersing the modified graphene nanosheet in an ethylene-vinyl alcohol copolymer matrix to obtain a flame-retardant barrier agent;
[0010] Step 3: adopting an eleven-layer co-extrusion blow molding film-forming process to prepare a high-barrier recyclable PE packaging film with a thickness of 50 to 200 μm; the high-barrier recyclable PE packaging film contains the flame-retardant barrier agent in step 2.
[0011] Preferably, a flame retardant light stabilizer is added to the flame retardant barrier agent;
[0012] The chemical structural formula of the flame retardant light stabilizer is:
[0013]
[0014] Preferably, the preparation method of the flame retardant cross-linking monomer is:
[0015] Step S3-1: generating a DOPO-based tertiary amine monomer by esterifying the carboxyl functional group of [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinic acid with the hydroxyl functional group of 3-dimethylamino-1-propanol;
[0016] Step S3-2: utilizing the nucleophilic substitution reaction mechanism, the tertiary amine group of the DOPO-based tertiary amine monomer undergoes a quaternization reaction with the bromine functional group of 3-bromopropyltrimethoxysilane to generate a flame-retardant crosslinking monomer.
[0017] Preferably, the preparation method of the flame retardant light stabilizer is:
[0018] Step S4-1: using a nucleophilic substitution reaction mechanism, the chlorine atom in thionyl chloride is catalyzed by N,N-dimethylformamide to replace the hydroxyl group in the carboxyl functional group of [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinic acid to generate [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinyl chloride;
[0019] Step S4-2: The acyl chloride group of [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinyl chloride reacts with the phenolic hydroxyl functional group of the ultraviolet absorber UV-0 (2,4-dihydroxybenzophenone) to generate a flame retardant light stabilizer.
[0020] Preferably, the formula and dosage of the high barrier recyclable PE packaging film are as follows:
[0021] First layer: the formula is 20-80wt% LDPE + 20-80wt% LLDPE, the dosage is 5-15wt%;
[0022] The second layer: the formula is 20-60wt% HDPE + 40-80wt% m-LLDPE, the dosage is 3-10wt%;
[0023] The third layer: the formula is 20-60wt% LDPE + 40-80wt% m-LLDPE, the dosage is 5-15wt%;
[0024] The fourth layer: the formula is 100wt% PE-g-MAH, the dosage is 1-5wt%;
[0025] The fifth layer: the formula is 95-99wt% LDPE + 1-5wt% EVOH, the dosage is 5-15wt%;
[0026] The sixth layer: the formula is 90-99wt% LDPE + 1-10wt% functional barrier material, the dosage is 10-40wt%;
[0027] The seventh layer: the formula is 95-99wt% LDPE + 1-5wt% EVOH, the dosage is 5-15wt%;
[0028] The eighth layer: the formula is 100wt% PE-g-MAH, the dosage is 1-5wt%;
[0029] Ninth layer: 20-60wt% LDPE + 40-80wt% m-LLDPE, dosage is 5-15wt%;
[0030] The tenth layer: the formula is 20-60wt% HDPE + 40-80wt% m-LLDPE, the dosage is 3-10wt%;
[0031] The eleventh layer: the formula is 20-80wt% LDPE+20-80wt% LLDPE, and the dosage is 5-15wt%.
[0032] Preferably, the hydroxylated graphene powder has a sheet diameter of 1.3 μm and a thickness of 1.5 nm.
[0033] The water vapor permeability of a high barrier recyclable PE packaging film prepared according to the above process is 0.5-2.0 [g / (m 2 ·24h)], oxygen permeability is 0.5~1.5[cm 3 / (m 2 ·24h·0.1MPa)].
[0034] The application of a high-barrier recyclable PE packaging film prepared according to the above process in the field of dairy product packaging.
[0035] Beneficial effects:
[0036] The present invention first synthesizes a flame retardant cross-linking monomer, uses the flame retardant cross-linking monomer to perform surface modification on an inorganic raw material graphene nanosheet, and then compounds it with an organic ethylene vinyl alcohol copolymer to obtain a barrier agent, introduces the barrier agent into the raw material of a PE co-extrusion film, and adopts an eleven-layer co-extrusion blow molding film-forming process to prepare a PE packaging film;
[0037] The experimental results show that the PE packaging film prepared by the present invention has excellent barrier properties as well as excellent light-blocking and flame-retardant properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a synthetic route for flame retardant cross-linking monomers;
[0039] Figure 2 It is a synthetic route for flame retardant light stabilizers;
[0040] Figure 3 These are the performance test results of the eleven-layer co-extruded film. DETAILED DESCRIPTION
[0041] The present invention uses inorganic raw material graphene nanosheets with excellent barrier properties and organic raw material ethylene vinyl alcohol copolymer as composite modifiers. In order to eliminate the agglomeration effect during the composite process of the inorganic graphene nanosheets and the organic ethylene vinyl alcohol copolymer, the present invention designs and synthesizes a cross-linking monomer, and first uses the cross-linking monomer to modify the surface of the graphene nanosheets. The modified graphene nanosheets can be dispersed more evenly when composited with the ethylene vinyl alcohol copolymer, thereby achieving the technical improvement goal of exerting the synergistic barrier of the inorganic raw material graphene nanosheets and the organic raw material ethylene vinyl alcohol copolymer.
[0042] Experimental example:
[0043] R&D experiment 1:
[0044] In order to improve the dispersion performance of graphene nanosheets and give packaging materials a certain flame retardant ability, the present invention develops and synthesizes a flame retardant cross-linking monomer;
[0045] Preparation of flame retardant cross-linking monomers, such as Figure 1 As shown, the preparation steps are:
[0046] Step 1: The carboxyl functional group of [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinic acid reacts with the hydroxyl functional group of 3-dimethylamino-1-propanol to generate a DOPO-based tertiary amine monomer;
[0047] Step 2: utilizing the nucleophilic substitution reaction mechanism, the tertiary amine group of the DOPO-based tertiary amine monomer undergoes a quaternization reaction with the bromine functional group of 3-bromopropyltrimethoxysilane to generate a flame-retardant cross-linking monomer;
[0048] The specific experimental steps for preparing the flame retardant cross-linking monomer are as follows:
[0049] 3.5 g of [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinic acid, 2.0 g of 3-dimethylamino-1-propanol and 60 mL of cyclohexane were added into a three-necked flask, 2 mL of concentrated sulfuric acid was added dropwise into the three-necked flask under mechanical stirring, the temperature was raised to 85° C. and refluxed for 4 h, cyclohexane was recovered by reduced pressure distillation, and the mixture was washed with saturated sodium bicarbonate aqueous solution and deionized water in sequence until neutral, filtered, and dried to obtain a DOPO-based tertiary amine monomer;
[0050] 2.6 g of DOPO-based tertiary amine monomer and 30 mL of cyclohexane were added to a three-necked flask, and the temperature was raised to 40° C. under nitrogen protection and mechanical stirring. After the temperature stabilized, 30 mL of 3-bromopropyltrimethoxysilane solution (prepared with 2.4 g of 3-bromopropyltrimethoxysilane and 30 mL of cyclohexane) was added dropwise to the three-necked flask, and the mixture was stirred at 40° C. for 12 h. After cooling, the mixture was rotary evaporated, washed with ethyl acetate, and vacuum dried to obtain a flame-retardant cross-linking monomer.
[0051] The flame retardant cross-linking monomer is characterized by hydrogen nuclear magnetic resonance spectrum: 1 H NMR (CDCl3, 400MHz) δ: 0.67-0.75 (m, 4H), 1.67-1.78 (m, 4H), 2.05-2.17 (m, 4H), 2.67-2. 86 (m, 5H), 3.31 (s, 12H), 3.52-3.64 (m, 26H), 4.10-4.16 (m, 4H), 7.25-8.13 (m, 8H, Ar-H).
[0052] R&D experiment 2:
[0053] In order to extend the service life of packaging materials, protect packaging materials from the influence of light aging, and give packaging materials a certain flame retardant ability, the present invention develops and synthesizes a flame retardant light stabilizer;
[0054] Preparation of flame retardant light stabilizers, such as Figure 2 As shown, the preparation steps are:
[0055] Step 1: Using the nucleophilic substitution reaction mechanism, the chlorine atom in thionyl chloride is catalyzed by N,N-dimethylformamide to replace the hydroxyl group in the carboxyl functional group of [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinic acid to generate [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinyl chloride;
[0056] Step 2: The acyl chloride group of [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinyl chloride reacts with the phenolic hydroxyl functional group of the ultraviolet absorber UV-0 (2,4-dihydroxybenzophenone) to generate a flame retardant light stabilizer;
[0057] The specific experimental steps for preparing flame retardant light stabilizer are as follows:
[0058] 3.5 g of [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinic acid and 50 mL of dichloromethane were added to a three-necked flask, and 2.3 mL of thionyl chloride and 2 drops of N,N-dimethylformamide were added dropwise to the three-necked flask in sequence under mechanical stirring, and the temperature was raised to 45° C. and refluxed for 6 h. The mixture was cooled to room temperature, and the solvent was removed by distillation under reduced pressure. After drying, [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinyl chloride was obtained;
[0059] 1.9 g of [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinyl chloride, 2.2 g of 2,4-dihydroxybenzophenone, and 60 mL of dichloromethane were added to a three-necked flask, and then 2.1 mL of triethylamine was slowly added dropwise to the three-necked flask, and the mixture was stirred at room temperature for 18 h, and washed with 1 mol / L hydrochloric acid, 5 wt% sodium bicarbonate aqueous solution, and saturated sodium chloride aqueous solution in sequence, and the solvent was removed by distillation under reduced pressure, and a flame retardant light stabilizer was obtained after drying;
[0060] The nuclear magnetic resonance hydrogen spectrum of the flame retardant light stabilizer is characterized as follows: 1 H NMR (CDCl3, 400MHz) δ: 2.71-3.19 (m, 5H), 6.80-8.13 (m, 24H, Ar-H).
[0061] Embodiment 1:
[0062] (1) preparing modified graphene nanosheets I, wherein the preparation method is as follows: modifying graphene nanosheets (graphene nanosheets having hydroxyl groups on their surfaces) with flame-retardant cross-linking monomers to obtain modified graphene nanosheets I, wherein the specific experimental steps are as follows: adding 1 g of hydroxylated graphene powder, 80 mL of anhydrous ethanol and 20 mL of deionized water into a beaker, ultrasonically treating for 10 min, heating to 40° C., adding 2 g of the flame-retardant cross-linking monomer into the beaker, stirring for 10 h, centrifuging, and repeatedly centrifuging and washing with anhydrous ethanol and deionized water, and vacuum drying to obtain modified graphene nanosheets I;
[0063] A functional barrier material I is prepared, and the preparation method thereof is as follows: dispersing modified graphene nanosheets I in an ethylene-vinyl alcohol copolymer matrix to prepare the functional barrier material I, and the specific experimental steps are as follows: adding 20 g of ethylene-vinyl alcohol copolymer resin and 3 g of modified graphene nanosheets I into a twin-screw extruder, and blending, melting, extruding, and pelletizing the twin-screw extruder to prepare the functional barrier material I;
[0064] (2) preparing modified graphene nanosheets II, wherein the preparation method comprises: modifying graphene nanosheets (graphene nanosheets having hydroxyl groups on their surfaces) by using flame retardant crosslinking monomers and flame retardant light stabilizers to obtain modified graphene nanosheets II, wherein the specific experimental steps refer to the preparation experiment of modified graphene nanosheets I, and the difference is only that 2g of the flame retardant crosslinking monomer is replaced by 1g of the flame retardant crosslinking monomer and 1g of the flame retardant light stabilizer;
[0065] A functional barrier material II is prepared, and the preparation method thereof is as follows: dispersing the modified graphene nanosheet II in an ethylene-vinyl alcohol copolymer matrix to prepare the functional barrier material II. The specific experimental steps refer to the preparation experiment of the functional barrier material I, and the only difference is that the modified graphene nanosheet II is used to replace the modified graphene nanosheet I;
[0066] (3) preparing a blended barrier material, wherein the preparation method is as follows: directly dispersing graphene nanosheets in an ethylene-vinyl alcohol copolymer matrix to prepare the blended barrier material. The specific experimental steps refer to the preparation experiment of the functional barrier material I, and the only difference is that the modified graphene nanosheet I is replaced by the graphene nanosheet;
[0067] Among them, ethylene-vinyl alcohol copolymer resin (EVOH) was purchased from Guangzhou Best New Material Technology Co., Ltd., and its brand is ET3803RB; hydroxylated graphene powder was purchased from Sichuan Kenye Technology Development Co., Ltd., and its specifications are: average flake diameter is 2 μm, and average thickness is 3 nm.
[0068] Embodiment 2:
[0069] (1) Preparing an eleven-layer co-extruded film I, comprising the following steps:
[0070] Step 1: Set the eleven-layer co-extruded film I to be an eleven-layer symmetrical film structure, and the formula and dosage of each film layer are as follows:
[0071] First layer: formula is 50wt% LDPE + 50wt% LLDPE, dosage is 10wt%;
[0072] The second layer: the formula is 40wt% HDPE + 60wt% m-LLDPE, the dosage is 5wt%;
[0073] The third layer: the formula is 40wt% LDPE + 60wt% m-LLDPE, the dosage is 10wt%;
[0074] The fourth layer: the formula is 100wt% PE-g-MAH, the dosage is 2.5wt%;
[0075] The fifth layer: the formula is 98wt% LDPE + 2wt% EVOH, the dosage is 10wt%;
[0076] The sixth layer: the formula is 95wt% LDPE + 5wt% functional barrier material I, the dosage is 25wt%;
[0077] The seventh layer: the formula is 98wt% LDPE + 2wt% EVOH, the dosage is 10wt%;
[0078] The eighth layer: the formula is 100wt% PE-g-MAH, the dosage is 2.5wt%;
[0079] The ninth layer: 40wt% LDPE + 60wt% m-LLDPE, dosage is 10wt%;
[0080] The tenth layer: the formula is 40wt% HDPE + 60wt% m-LLDPE, the dosage is 5wt%;
[0081] Eleventh layer: the formula is 50wt% LDPE + 50wt% LLDPE, the dosage is 10wt%;
[0082] Step 2, each raw material in step 1 is respectively put into the hopper of eleven screw extruders of the eleven-layer co-extrusion film blowing unit, after stirring and mixing, the molten resin is merged at the head of the die through a splitter, extruded and blown through a die head, cooled, and rolled to obtain an eleven-layer co-extrusion film I with a thickness of 100 μm;
[0083] Among them, the process parameters of the screw extruder corresponding to the first, second, third, ninth, tenth and eleventh layers are set as follows: the temperature of zones 1-3 is 120°C, 150°C and 170°C respectively, the flow channel temperature is 165°C, and the speed is 30r / min;
[0084] The process parameters of the screw extruder corresponding to the fourth and eighth layers were set as follows: the temperatures of zones 1-3 were 125°C, 150°C, and 165°C, respectively, the flow channel temperature was 160°C, and the rotation speed was 15 r / min;
[0085] The process parameters of the screw extruders corresponding to the fifth, sixth, and seventh layers were set as follows: the temperatures of zones 1-3 were 140°C, 160°C, and 180°C, respectively, the flow channel temperature was 175°C, and the rotation speed was 40 r / min;
[0086] Among them, low-density polyethylene resin (LDPE) was purchased from Jiangsu Rantai Plastic Co., Ltd., and its brand is LD 150DW; linear low-density polyethylene resin (LLDPE) was purchased from Yuyao Hongyang Plastic Co., Ltd., and its brand is 2045G; high-density polyethylene resin (HDPE) was purchased from Dongguan Longhuang Plastic Raw Materials Co., Ltd., and its brand is FB5600; metallocene polyethylene resin (m-LLDPE) was purchased from Dongguan Jinshixiang Plastic Raw Materials Co., Ltd., and its brand is SP4020; maleic anhydride grafted polyethylene resin (PE-g-MAH) was purchased from Dongguan Taotao Plastic Raw Materials Co., Ltd., and its brand is 4288.
[0087] (2) Preparation of eleven-layer co-extruded film II: Only the functional barrier material II is used to replace the functional barrier material I in the eleven-layer co-extruded film I, and the rest of the parts are the same as the eleven-layer co-extruded film I, thereby preparing the eleven-layer co-extruded film II.
[0088] (3) Preparation of eleven-layer co-extruded film a: Only the functional barrier material I in the eleven-layer co-extruded film I is replaced by the blended barrier material, and the rest of the parts are the same as those of the eleven-layer co-extruded film I, to prepare an eleven-layer co-extruded film, which is used as comparative example 1.
[0089] (4) Preparation of eleven-layer co-extruded film b: Only EVOH resin is used to replace the functional barrier material I in the eleven-layer co-extruded film I, and the rest of the parts are the same as the eleven-layer co-extruded film I, to prepare the eleven-layer co-extruded film b, which is used as comparative example 2.
[0090] Performance Test:
[0091] (1) Barrier properties: The barrier properties of the samples were tested using a Y110 oxygen permeability tester and a TC-03 water vapor permeability tester in accordance with GB / T 1038-2000 and GB / T 1037-2021 respectively;
[0092] (2) Flame retardant properties: A rectangular sample of 2 cm × 4 cm was fixed vertically and burned, and the ignition time of the sample was recorded;
[0093] (3) Light blocking performance: Lambda 950 UV-visible spectrophotometer was used to test the light transmittance of the samples in accordance with GB / T2410-2008. The test wavelength range was 250-800 nm, and the light transmittance of the samples at 380 nm was recorded.
[0094] (4) Mechanical properties: A 30 mm × 5 mm sample was fixed on an Instron 5565 universal tensile testing machine and subjected to a tensile test at a tensile rate of 5 mm / min. The tensile strengths in the longitudinal and transverse directions were recorded respectively.
[0095] The above experimental results are shown in Table 1 and Figure 3 .
[0096] Table 1 Performance test results of eleven-layer co-extruded film
[0097]
[0098]
[0099] Through comprehensive analysis of the above experimental results, the following conclusions can be drawn:
[0100] (1) The barrier agent obtained by first modifying graphene nanosheets with flame-retardant cross-linking monomers and then compounding them with ethylene vinyl alcohol copolymers has a significantly better effect on improving the barrier properties of packaging materials than the barrier agent obtained by direct physical blending.
[0101] (2) The present invention not only gives the packaging material excellent light-blocking and flame-retardant capabilities, but also improves the overall mechanical properties of the material.
Claims
1. A process for preparing a high barrier recyclable PE packaging film, characterized in that: The following steps are involved: Step 1: Synthesize a flame retardant cross-linking monomer, the chemical structure of which is: Step 2: Modifying the hydroxylated graphene powder with a flame-retardant cross-linking monomer to obtain a modified graphene nanosheet, and uniformly dispersing the modified graphene nanosheet in an ethylene-vinyl alcohol copolymer matrix to obtain a flame-retardant barrier agent; Step 3: adopting an eleven-layer co-extrusion blow molding film-forming process to prepare a high-barrier recyclable PE packaging film with a thickness of 50 to 200 μm; the high-barrier recyclable PE packaging film contains the flame-retardant barrier agent in step 2.
2. The process for preparing a high barrier recyclable PE packaging film according to claim 1, characterized in that: The flame retardant barrier agent contains a flame retardant light stabilizer; The chemical structural formula of the flame retardant light stabilizer is:
3. The process for preparing a high barrier recyclable PE packaging film according to claim 1, characterized in that: The preparation method of the flame retardant cross-linking monomer is: Step S3-1: generating a DOPO-based tertiary amine monomer by esterifying the carboxyl functional group of [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinic acid with the hydroxyl functional group of 3-dimethylamino-1-propanol; Step S3-2: utilizing the nucleophilic substitution reaction mechanism, the tertiary amine group of the DOPO-based tertiary amine monomer undergoes a quaternization reaction with the bromine functional group of 3-bromopropyltrimethoxysilane to generate a flame-retardant crosslinking monomer.
4. The process for preparing a high barrier recyclable PE packaging film according to claim 2, characterized in that: The preparation method of the flame retardant light stabilizer is: Step S4-1: using a nucleophilic substitution reaction mechanism, the chlorine atom in thionyl chloride is catalyzed by N,N-dimethylformamide to replace the hydroxyl group in the carboxyl functional group of [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinic acid to generate [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinyl chloride; Step S4-2: The acyl chloride group of [(6-oxo-6H-dibenzo[C,E][1,2]oxaphosphorin-6-yl)methyl]succinyl chloride reacts with the phenolic hydroxyl functional group of the ultraviolet absorber UV-0 (2,4-dihydroxybenzophenone) to generate a flame retardant light stabilizer.
5. The process for preparing a high barrier recyclable PE packaging film according to claim 1, characterized in that: The formula and dosage of the high barrier recyclable PE packaging film are as follows: First layer: the formula is 20-80wt% LDPE + 20-80wt% LLDPE, the dosage is 5-15wt%; The second layer: the formula is 20-60wt% HDPE + 40-80wt% m-LLDPE, the dosage is 3-10wt%; The third layer: the formula is 20-60wt% LDPE + 40-80wt% m-LLDPE, the dosage is 5-15wt%; The fourth layer: the formula is 100wt% PE-g-MAH, the dosage is 1-5wt%; The fifth layer: the formula is 95-99wt% LDPE + 1-5wt% EVOH, the dosage is 5-15wt%; The sixth layer: the formula is 90-99wt% LDPE + 1-10wt% functional barrier material, the dosage is 10-40wt%; The seventh layer: the formula is 95-99wt% LDPE + 1-5wt% EVOH, the dosage is 5-15wt%; The eighth layer: the formula is 100wt% PE-g-MAH, the dosage is 1-5wt%; Ninth layer: 20-60wt% LDPE + 40-80wt% m-LLDPE, dosage is 5-15wt%; The tenth layer: the formula is 20-60wt% HDPE + 40-80wt% m-LLDPE, the dosage is 3-10wt%; The eleventh layer: the formula is 20-80wt% LDPE+20-80wt% LLDPE, and the dosage is 5-15wt%.
6. The process for preparing a high barrier recyclable PE packaging film according to claim 1, characterized in that: The hydroxylated graphene powder has a sheet diameter of 1.3 μm and a thickness of 1.5 nm.
7. A high barrier recyclable PE packaging film prepared by the process according to any one of claims 1 to 6, characterized in that: The water vapor permeability of the high barrier recyclable PE packaging film is 0.5 to 2.0 [g / (m 2 ·24h)], oxygen permeability is 0.5~1.5[cm 3 / (m 2 ·24h·0.1MPa)].
8. Application of the high barrier recyclable PE packaging film according to claim 7 in the field of dairy product packaging.
Citation Information
Patent Citations
Preparation method and application of nano composite flame retardant containing DOPO and delamination graphene
CN103073749A
Synthesis method of 6-oxo-6H-dibenzo(c, e)(1, 2)oxaphosphorin-6-keto-butanedioic acid
CN104513277A
Marine biomass based flame retardant with cellulose-like structure
CN106008742A
Phosphor-rich graphene flame-retardant agent and preparation method thereof
CN106883450A
Macromolecular flame retardant, preparation method and application thereof
CN112812285A
Cited By
Eleven-layer high-barrier polyethylene co-extruded film for sanitary towel packaging and preparation process
CN119773217A
